Mucormycosis in patients with COVID‐19: A cross‐sectional descriptive multicentre study from Iran. Issue 10 (1st July 2021) - Pakdel, Farzad; Ahmadikia, Kazem; Salehi, Mohammadreza; Tabari, Azin; Jafari, Rozita; Mehrparvar, Golfam; Rezaie, Yasaman; Rajaeih, Shahin; Alijani, Neda; Barac, Aleksandra; Abdollahi, Alireza; Khodavaisy, Sadegh
Abstract: Purpose: The aim of the study was to report clinical features, contributing factors and outcome of patients with coronavirus disease 2019 (COVID‐19)‐associated mucormycosis (CAM). Methods: A cross‐sectional descriptive multicentre study was conducted on patients with biopsy‐proven mucormycosis with RT‐PCR‐confirmed COVID‐19 from April to September 2020. Demographics, the time interval between COVID‐19 and mucormycosis, underlying systemic diseases, clinical features, course of disease and outcomes were collected and analysed. Results: Fifteen patients with COVID‐19 and rhino‐orbital mucormycosis were observed. The median age of patients was 52 years (range 14–71), and 66% were male. The median interval time between COVID‐19 disease and diagnosis of mucormycosis was seven (range: 1–37) days. Among all, 13 patients (86%) had diabetes mellitus, while 7 (46.6%) previously received intravenous corticosteroid therapy. Five patients (33%) underwent orbital exenteration, while seven (47%) patients died from mucormycosis. Six patients (40%) received combined antifungal therapy and none that received combined antifungal therapy died. Conclusion: Clinicians should be aware that mucormycosis may be complication of COVID‐19 in high‐risk patients. Poor control of diabetes mellitus is an important predisposing factor for CAM. Systematic surveillance for control of diabetes mellitus and educating physician about the early diagnosis of CAM are suggested.